Homozygous Microdeletion Involving Exon 1 of ERCC8 and NDUFAF2 With Uniparental Isodisomy of Chromosome 5 - Kaori Yamoto; Kosuke Yamada; Kenji Shimizu; Sachiko Miyamoto; Mitsuko Nakashima; Hirotomo Saitsu (Molecular Genetics & Genomic Medicine)
ABSTRACT Background Uniparental isodisomy (UPiD) refers to a condition, in which both homologous chromosomes are inherited from only one parental homolog, which can result in either imprinting disorders or autosomal recessive conditions. Methods We performed chromosomal microarray analysis, exome sequencing (ES), and RNA sequencing (RNA‐seq) using the patient's urine‐derived cells on a patient with growth retardation and multiple congenital anomalies. Results We identified a homozygous ~0.53 kb microdeletion at 5q12.1, which was transmitted from the father with paternal UPiD(5). The deletion encompassed the first exon of both the ERCC8 and NDUFAF2 genes, which are responsible for Cockayne syndrome (CS) and mitochondrial complex I deficiency, respectively. Furthermore, RNA‐seq confirmed the reduced expression of both genes. Indeed, in addition to clinical features common to both syndromes, such as growth retardation, developmental delay, and feeding difficulties, the patient exhibited blended phenotypes: the characteristic features of CS, including arthrogryposis, microcephaly, and facial dysmorphisms, and those of mitochondrial complex I deficiency, including high serum lactate levels and lethal apnea resulting in a severe clinical course. Conclusion The results imply that ES in combination with RNA‐seq could be a powerful method for the detection of underlying factors responsible for rare genetic conditions, such as UPD.